Methods and strategies of organizational conflict management inside educational institutions: an analytical descriptive study أساليب وإستراتيجيات إدارة المشكلات التنظيمية داخل المؤسسات التعليمية - Alhadidi, Ibrahim Ali Mubarak; Al-Hidabi, Dawood Abdulmalek Yahya (2019)
This descriptive research discusses the organizational conflict management in educational institutions. The statement problem; identified the need for schools to learn management techniques and organizational strategies for conflict management, which may arise somewhat within the schools. The research objectives are: to understand the concepts of organizational conflict, its causes in the organization, the methods and strategies used by administrations in general and school administrations in particular in managing organizational conflict in them. Through the descriptive analytical approach, the research reached a number of findings: The method of cooperation in the Organization is one of the best methods used, because of its good impact in the soul, and improve the work. Complementary, avoidance and power usage methods can be used; depending on the type of problem. The participatory approach promotes a culture of interest in the interests of the Organization and respect for views among the members of the Organization.